TRADISI “BERZANJEN” MASYARAKAT BANYUWANGI KAJIAN RESEPSI SASTRA TERHADAP TEKS ALBARZANJI - Hasim Ashari (Universitas Gadjah Mada, 2012)
Indonesia Muslim society. In Banyuwangi, East Java, the text is quite popular. People of Banyuwangi recite the text for several occasions, such as wedding ceremonies, circumcision, childbirths, the celebrations of the Prophet’s birthday, and so forth. Recitation of the text has been a form of art performance. These practices show are a manifestation of the transformation of Arabic and Islamic culture in Banyuwangi, which have contributed signi cantly to culturasl changes in Banyuwangi, East Java.